Managing and controlling design process issues by using stepwise approach modelling - Abdelrafe, Elzamly; Burairah, Hussin; Norhaziah, Md Salleh; Abdul Samad, Shibghatullah (Maxwell Scientific Publications Corp., 2016)
The objective of study is to introduce stepwise regression approach modelling to mitigate and manage the software design process issues in software project by using proposed controls. In addition, the software design process issues were controlled and modelled by using stepwise regression approach except risk 3. Furthermore, we illustrated the design process issues were mitigated by control techniques in Table 40. However, we need to combine more techniques and artificial optimal algorithms to mitigate the issues in software design process.